2015
DOI: 10.1093/mnras/stv2265
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of compact, massive subsystems in stellar clusters and its relation with intermediate-mass black holes

Abstract: During their evolution, star clusters undergo mass segregation, by which the orbits of the most massive stars shrink, while the lighter stars move outwards from the cluster centre. In this context, recent observations and dynamical modelling of several galactic and extra-galactic globular clusters (GCs) suggest that most of them show, close to their centre, an overabundance of mass whose nature is still matter of debate. For instance, many works show that orbitally segregated stars may collide with each other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 101 publications
2
32
0
Order By: Relevance
“…The difference in the values of M/L that we find here with respect to those by de Vita et al (2016) is in line with the difference among the global values of M/L listed in Table 3. Arca-Sedda (2016) proposed an analysis of numerical simulations showing that the excess of mass in the centre of a cluster could be due to the presence of a subsystem of heavy remnants orbitally segregated, and not to an IMBH. In particular, for the globular cluster ω Cen they estimate a mass of (1.45 ± 0.03) × 10 3 M ⊙ for the central component of massive remnants, assuming a total mass of 2.5 × 10 6 M ⊙ for the cluster.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…The difference in the values of M/L that we find here with respect to those by de Vita et al (2016) is in line with the difference among the global values of M/L listed in Table 3. Arca-Sedda (2016) proposed an analysis of numerical simulations showing that the excess of mass in the centre of a cluster could be due to the presence of a subsystem of heavy remnants orbitally segregated, and not to an IMBH. In particular, for the globular cluster ω Cen they estimate a mass of (1.45 ± 0.03) × 10 3 M ⊙ for the central component of massive remnants, assuming a total mass of 2.5 × 10 6 M ⊙ for the cluster.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Pasham et al, 2014;Wrobel et al, 2016;Earnshaw et al, 2016;Arca-Sedda, 2016). Kiziltan et al (2017) found an indirect evidence for an IMBH of about 2200 M ⊙ at the center of the globular cluster 47 Tucanae based on the dynamical state constrained by the timing data of millisecond pulsars.…”
Section: Working Definition Of a (Supermassive) Black Holementioning
confidence: 99%
“…Yokoyama 1997;Düchting 2004), or from runaway stellar collisions (e.g. Giersz et al 2015;Arca-Sedda 2016), or as the remnants of population III stars (e.g. Ricotti 2016) for example and how they are fuelled (from stellar winds, via Bondi accretion, or from Roche lobe overflow, for example Miller & Hamilton 2002;Miller & Colbert 2004).…”
Section: Introductionmentioning
confidence: 99%